The Chico Mendes Extractive Reserve: trajectories of agro-extractive development in Amazonia - Wallace, Richard H.; Gomes, Carlos Valério A.; Cooper, Natalie A. (Desenvolvimento e Meio Ambiente, 2018)
The Chico Mendes Extractive Reserve (CMER) located in Acre, Brazil in the southwest Amazon is a powerful symbol of the rubber tapper social movement. Created in 1990, the Reserve is named after rubber tapper and union leader Francisco “Chico” Mendes, who was assassinated by ranchers in 1988. The concept of the extractive reserve, a type of sustainable-use protected area, was conceived by rubber tappers to secure land rights and to protect the forests from which they derived their livelihoods. Thirty years since its creation, non-timber forest product (NTFP) extraction maintains a critical role in CMER resident livelihoods, but it is now one of multiple and dynamic trajectories of income generating activities in the CMER. The state government has promoted sustainable development policies aimed at productive and multiple use of forests, including community-based timber management (CBTM). Concomitantly, the scale and scope of small-scale cattle ranching reflecting a growing “cowboy culture” pervasive in Eastern Acre is growing. These forces have brought sociocultural changes to the reserve as CMER residents engage these intertwined trajectories to improve their livelihoods. This article explores the trajectories of multiple development strategies in the CMER. We do this by revisiting and expanding on the principal themes of research of the co-authors – NTFP extraction, cattle ranching, and CBTM. Increasingly diverse CMER households demand multiple pathways to improve livelihoods, and these trajectories have created new economic opportunities for reserve residents. Although the NTFP sector has experienced some success in market development and valued-added initiatives, investments have not produced a sustainable and diversified extractive sector. Cattle ranching and CBTM have provided economic benefits to reserve residents’ livelihoods, but they have also created internal tensions across the social movement and governments agencies. A strategic vision is required that brings diverse government, non-government and reserve residents together and articulates how these dynamic, linked, and sometimes conflicting trajectories can synergize within a balanced, diversified livelihood framework to ensure long-term sustainability of the CMER.